The Effect of Celebrity Endorsement on Repurchase Intention With Brand Attitude, Brand Credibility, and Brand Image as Intervening Variables on Product Somethinc - Arismunandhar Sunarwia, Atdriansyah; Rahman Kadir, Abdul; Maming, Djumidah; Kadir, Nuraeni; A.S. Parawansa, Dian; Mustafa, Fahrina (PT. Maju Malaqbi Makkarana, 2023)
By taking into account the function of brand attitude, brand credibility, and brand image as intervening variables, this study seeks to assess the impact of celebrity endorsement on repurchase intention of SOMETHINC products. A common marketing tactic for influencing consumer views and behavior toward specific products is celebrity endorsement. This study employs a survey methodology, collecting information from participants using questionnaires that are given to those who are familiar with SOMETHINC goods and have interacted with relevant celebrity endorsements. Utilizing statistical analysis techniques like multiple linear regression and path analysis, hypotheses are tested. The findings demonstrated that brand attitude, brand credibility, and brand image are significantly influenced by celebrity endorsement. In this situation, brand attitude has been shown to mediate between celebrity endorsement and intention to repurchase. A similar association between celebrity endorsement and repurchase intention is mediated by brand credibility and brand image. These results demonstrate that celebrity endorsements can positively affect consumers' perceptions of SOMETHINC products by enhancing brand attitude, brand credibility, and brand image. These factors in turn influence consumers' desire to repurchase the product. In order to maximize the efficacy of this marketing strategy, businesses should carefully evaluate the choice and management of celebrity endorsements as well as the development of positive brand attitudes, brand credibility, and brand image.